Measuring the efficiency of physical education among primary school students during learning athletics (Training and Practice : Journal of Educational Sciences, 2018)
A teacher specialized in physical education and sports is going to teach athletics in school as well. Athletics is a part of physical education and its divisions are based on natural movements and capabilities. By these movements the level of motoric skills of students, their level of training and physical health may be measured. Education for healthy lifestyle plays an important role in the life of the next generations. In order to improve the efficiency of physical education in schools, we need to seek the platforms of development, which may enhance future results. We need to plan sports lessons based on skill differentiation and personal capabilities. Our aim is to build up a system of physical education, which suits the personal training level of students and yields the best possible results.